2007
DOI: 10.2320/matertrans.mra2006355
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of Grain Refinement and Spherical Shaped Precipitate Dispersions in Fracture Toughness of a Mg-Zn-Zr Alloy

Abstract: Fracture toughness was examined on a commercial Mg-Zn-Zr alloy, ZK60. The commercial alloy was extruded at a temperature of 493 K to obtain fine grain structures having fine spherical shaped precipitates. The microstructures consisted of equi-axed grains. The average grain size and the precipitate diameter were about 3 mm and 25 $ 50 nm, respectively. The yield strength and elongation-to-failure were 287 MPa and 26.7%, respectively. The plane-strain fracture toughness, K IC , was estimated to be 34.8 MPam 1=2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…1) Die casting and injection molding are the main method of manufacturing such components, 2) however, plastic forming technologies such as hot drawing and hot forging with high productivity have been developed to form thinner walls of the components without defects. 3,4) In the drawing process, it has been clearly demonstrated that the critical strain rate increase with the refinement of grain size in AZ31 magnesium alloy at 523 K. 5) Thus, grain size refinement of magnesium alloys is essential not only for the development of superior mechanical properties at room temperature such as higher strength, toughness 6,7) and ductility, 8) but also for the higher productivity. In general, dynamic restoration behavior is dependent on the stacking fault energy (SFE) and lattice diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…1) Die casting and injection molding are the main method of manufacturing such components, 2) however, plastic forming technologies such as hot drawing and hot forging with high productivity have been developed to form thinner walls of the components without defects. 3,4) In the drawing process, it has been clearly demonstrated that the critical strain rate increase with the refinement of grain size in AZ31 magnesium alloy at 523 K. 5) Thus, grain size refinement of magnesium alloys is essential not only for the development of superior mechanical properties at room temperature such as higher strength, toughness 6,7) and ductility, 8) but also for the higher productivity. In general, dynamic restoration behavior is dependent on the stacking fault energy (SFE) and lattice diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the selection of a suitable alloying element or secondary particles into the PM Mg alloy is also essential. Considering that the extruded ZK60 alloy containing hard MgZn 2 phase particles usually exhibit good ductility ( 415%) [7], fabricating an ultrahigh-strength and high-ductility ZK60 alloy via PM processing is possible. Besides, the correlation between the microstructure and tensile behavior in the PM ZK60 alloy was discussed briefly.…”
Section: Introductionmentioning
confidence: 99%
“…34) The dislocation movement is easily interrupted, as does a conventional second-phase particle, regardless of the interface structures. In the fracture toughness test, recent studies have also shown that the quasicrystalline phase particle 20) and the precipitate particle 7) have a role of pinning the dislocation movements. However, the interface structures affect the nucleation site for void formation when the strains are increased: the fracture occurs at the interface between the matrix and the particle or in the particle itself, for the particle consisting of an incoherent interface.…”
Section: )mentioning
confidence: 99%
“…5,6) In addition, the dispersion of fine spherical shaped precipitates enhances the fracture toughness by pinning the dislocation movements around them. 7,8) Controlling the grain refinement and/or the presence of precipitates in the matrix are clearly effective methods for improving the fracture toughness in magnesium and magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%